Penerapan Metode Multi-Objective Optimization on The Basic of Ratio Analysis (MOORA) Dalam Seleksi Siswa Unggulan Sekolah - Fifto Nugroho; Harmayani Harmayani; Mesran Mesran; Rabli Hari Mulia; Eko Maruli Tua Situmorang; Ricard Ricardo (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
This study aims to determine the superior students in a school based on the achievements of the students. To solve this problem, the writer uses the Multi-Objective Optimization on The Basic of Ratio Analysis (MOORA) method. MOORA is a relatively simple method that can rank a number of alternatives by subtracting the previously weighted benefit and cost criteria. The results showed that the highest ranking value was found in alternative A1 with a result of 0.1906 and followed by alternative A2 with a result of 0.1901.